Assessment of oil and seed meal quality parameters of rapeseed-mustard group of crops - CHAUHAN, J S; KUMAR, SATYANSHU (The Indian Journal of Agricultural Sciences, 2011)
Oil, protein, glucosinolates, fibre content and fatty acid profile were investigated in 43 rapeseed-mustard varieties. Oil content ranged from 36.5 % in karan rai variety ‘PC 5’ to 43.5 % in ‘Jhumka’, a yellow sarson variety. The maximum (20.7%) and minimum (17.6%) protein content was recorded for a variety of ‘GSL 1’ gobhi sarson (‘GSL 1’) and ‘Jhumka’ yellow sarson, respectively. A wide variation was observed for different fatty acids. Gobhi sarson varieties (‘Neelam’ and ‘Sheetal’) and of brown sarson (‘KBS 3’) had oleic acid in the range of 22.5–32.2 %. The oleic to linoleic and ω-6 to ω-3 fatty acid ratio were very low, the highest was 1.7 and 2.4, respectively. ‘GSL 1’ and ‘Sheetal’ of gobhi sarson; ‘Pusa Gold’ and ‘Jhumka’ of yellow sarson showed low level of linolenic acid (< 10%). Glucosinolates content in all the varieties was much higher than the desired level of < 30 μ moles / g defatted seed meal. Two varieties ‘RCC 4’ of Indian mustard and ‘Sheetal’ of gobhi sarson had glucosinolates < 50 μ moles / g defatted seed meal. Fibre content varied substantially ranging from 6.3–18.9 %. Contrary to the belief that yellow-seeded varieties had low fibre content, two yellow sarson varieties had the highest fibre content. Correlation studies revealed significant and negative association of oil with protein content (r = –0.566**), saturated fatty acid (r = –0.392*) and glucosinolates (r = –0.451**). Protein content and saturated fatty acid were positively and significantly correlated with each other (r = 0.335*). Oleic acid had positive and highly significant relationship with linoleic, eicosenoic, oleic to linoleic and ω-6 to ω-3 fatty acid ratio. Glucosinolates and fibre content did not show any relationship with any of the quality parameters investigated.